Local Government Forestry Expenditure and Forest Land Cover: A Preliminary Lesson from Decentralized Indonesia - Hidayati, Firda (UI Scholars Hub, 2016)
Even though government of Indonesia invests billions of rupiah to tackle deforestation, its effectiveness has been questionable. This study analyses changes in rates of forest cover in Indonesia and their association with forestry expenditures (FE) spent by the provincial governments. Based on 2007 to 2010 data, linear multiple regression results indicate that FE is not enough to tackle the negative change in forest land cover that could represent deforestation. Moreover, it was found that FE have negative association with forest land cover and therefore, can be associated to deforestation. This negative association remains when other factors that affect forest land cover such as wood extraction, agriculture outcome, forestry outcome, population growth and population density and initial environmental conditions have been controlled.